Studying antibacterial and antioxidant activity of total plant extracts and complexes composed by them (Experimental biology, 2018)
Actual problem of the modern medicine and pharmacology is replenishment of the list of chemically synthesized drugs by natural herbal medicines, which are derives on the basis of cooperative plant extracts or with use of the individual components isolated from them.  A lot of medicinal plants are widely used in pharmaceutics for the preparation of drugs, the action of which is directed at fighting infectious agents, protecting the body from the effects of free radicals. To develop such drugs, it is necessary to select a medicinal plant raw material containing biologically active components with a broad-spectrum of action. Such biologically active components can be represented by flavonoids and vitamin C, which are an ideal combination that possesses capillary-strengthening, anti-inflammatory, antiallergic, antibacterial, antioxidant activities. Particular interest is attracted to the selection of herbal complexes due to the synergistic action of components improving the current activity. Also they appears a new biological activities that allows to reach the greatest effectiveness and expansion of a range medicine’s effect.The objects of the study were dry extracts isolated from various parts of wild plants of Kazakhstan flora: Salvia deserta (Lamiaceae), Vexibia alopecuroides, Astragalus lanuginosus, Astragal sieversianus, Vicia subvillosa (Fabaceae), Platycladus orientalis  (Cupressaceae), Paeonia intermedia (Paeoniaceae), Veronica incana (Plantaginaceae), Linum pallescens (Linaceae), Conium maculatum (Apiaceae), Artemisia absinthium (Asteraceae).Extracts were obtained by the method of two-stage maceration. The amount of flavonoids and vitamin C was determined photometrically using aluminum chloride, ferric chloride and potassium ferricyanide, respectively. Studies of  the antimicrobial activity was determined by serial dilutions in broth for strains of microorganisms Staphylococcus aureus ATCC 29213, Pseudomonas aeruginosa ATCC 27853, Escherichia  coli ATCC 8739, Candida albicans ATTC 90028. The antioxidant potential of the extracts was determined photometrically using the ABTS • + radical cations.The extracts with the high content of flavonoids and vitamine C, which has therapeutically significant antioxidant potential, and the antibacterial and antifungal activities comparable with Ciprofloxacin and Amphotericin B antibiotics activity were revealed. Complexes of extracts with synergetic action were selected.  Complexes of total extracts Paeonia intermedia (roots, ethanol) + Paeonia intermedia (aerial part, ethanol), Platycladus orientalis (aerial part, ethanol) + Veronica incana (roots, ethanol), Paeonia intermedia (roots, ethanol) + Platycladus orientalis (aerial part, ethanol), Paeonia intermedia  (aerial part, ethanol) + Astragal sieversianus (roots, ethanol) are characterized by high synergistic action of the components with respect to two (antimicrobial and antioxidant) activities, promising for practical use.
Keywords: plant extracts, biological active compounds, antimicrobial activity, antioxidant activity, synergistic action.